HAMBATAN EVALUASI PEMBELAJARAN BERDIFERENSIASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Ikhwaturraiyuna, Ikhwaturraiyuna; Chairunisa, Siti; Sinaga, Regita; Nababan, Ayu; Laia, Yufema; Manjani, Nurhudayah (Jurnal Merah Putih Sekolah Dasar, 2025)
The Merdeka Curriculum emphasizes the importance of differentiated learning evaluation tailored to the needs, readiness, and characteristics of students. However, in its implementation in elementary schools, teachers still face various obstacles. This study aims to analyze the obstacles experienced by elementary school teachers in implementing differentiated learning evaluation based on the Merdeka Curriculum. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews and observations of elementary school teachers. Data analysis was conducted thematically to identify patterns and main themes of obstacles that arose. The results show that the main obstacles faced by teachers include limited conceptual understanding of differentiated evaluation, difficulties in designing varied evaluation instruments, low technological literacy in implementing evaluation, as well as high administrative workload and lack of managerial support. These findings emphasize the need to strengthen teacher competencies through continuous training, improve technological literacy, and provide adequate institutional support so that the implementation of differentiated learning evaluation in the Merdeka Curriculum can run optimally in elementary schools.